Numerical investigation of the vortical flow over delta wing and reverse delta wing - Omar, Ashraf Ali E.; Jamaluddin, Hani Ludin; Asrar, Waqar (2012)
This study aims to give some thoughts and initial understanding of passive wake vortex alleviation by introducing add-ons devices onto the aircraft, which are delta wing (DW) and reverse delta wing (RDW). However, as a preliminary investigation, the study has treated these devices separately from the aircraft in order to clearly visualize the wake vortex formation behind the wing as a standalone. Numerical simulations were performed for both DW and RDW at various angles of attack to investigate the characteristics of the vortices generated downstream. These vortices were investigated in terms of velocity vectors with its magnitude, vorticity contours, circulation distribution and streamlines. The results showed that as the angle of attack increases, the vorticity magnitude and circulation increase for both DW and RDW vortices. But RDW vortex exhibited a lower magnitude compared to DW vortex at angle of attack of 20º and 30º. It is also observed that delta wing (DW) generates stronger wake vortices with greater peak velocity than the wake vortices generated by reverse delta wing (RDW)